Population density of Ocypode gaudichaudii h. Milne Edwards & Lucas, 1843 (Decapoda: Ocypodidae) on sandy beaches of Guayas, Ecuador - Rodrigo-Calderón, Divy (2026)
Sandy beaches provide recreational and tourism services and offer coastal protection, in addition to serving as the habitat of the ghost crab Ocypode gaudichaudii H. Milne Edwards & Lucas, 1843, where its populations may be affected by human activities. In this regard, the population density and structure of O. gaudichaudii were assessed on four beaches in the province of Guayas, Ecuador, during May–June 2025, using the quadrat method to count burrows and measure burrow entrance diameter (BED) as an indirect estimator of the crab’s body size; a total of 832 burrows were evaluated. The results showed that Engabao was the beach with the highest number of organisms and the greatest variability in burrow opening diameter, suggesting a more representative and abundant population structure compared to the others. This study is a first step toward future assessments of the ecological status of the sandy beaches of the Ecuadorian mainland.